Dipeptidyl peptidase 1 inhibition as a potential therapeutic approach in neutrophil-mediated inflammatory disease - Chalmers, James D.; Kettritz, Ralph; Korkmaz, Brice (Frontiers in Immunology, 2023)
Neutrophils have a critical role in the innate immune response to infection and the control of inflammation. A key component of this process is the release of neutrophil serine proteases (NSPs), primarily neutrophil elastase, proteinase 3, cathepsin G, and NSP4, which have essential functions in immune modulation and tissue repair following injury. Normally, NSP activity is controlled and modulated by endogenous antiproteases. However, disruption of this homeostatic relationship can cause diseases in which neutrophilic inflammation is central to the pathology, such as chronic obstructive pulmonary disease (COPD), alpha-1 antitrypsin deficiency, bronchiectasis, and cystic fibrosis, as well as many non-pulmonary pathologies. Although the pathobiology of these diseases varies, evidence indicates that excessive NSP activity is common and a principal mediator of tissue damage and clinical decline. NSPs are synthesized as inactive zymogens and activated primarily by the ubiquitous enzyme dipeptidyl peptidase 1, also known as cathepsin C. Preclinical data confirm that inactivation of this protease reduces activation of NSPs. Thus, pharmacological inhibition of dipeptidyl peptidase 1 potentially reduces the contribution of aberrant NSP activity to the severity and/or progression of multiple inflammatory diseases. Initial clinical data support this view. Ongoing research continues to explore the role of NSP activation by dipeptidyl peptidase 1 in different disease states and the potential clinical benefits of dipeptidyl peptidase 1 inhibition.